Dasar–Dasar Keyakinan Kristen Yang Terkait Dengan Proses PAK - Kezia Almanda Oni Eki (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This article discusses how to become a PAK teacher who lives by adhering to the basics of the Christian Faith as the basis of our Christian Faith is God. The life of a PAK teacher must always have a close relationship with God through praise, worship, and personal fellowship with Him. PAK teachers must be able to be role models for students like Jesus who is an example for our lives. In Hebrews 11: 1 it is said that